Spiropyran-Based Drug Delivery Systems - Fagan, Andrew; Bartkowski, Michał; Giordani, Silvia (Frontiers in Chemistry, 2021)
Nanocarriers are rapidly growing in popularity in the field of drug delivery. The ability of nanocarriers to encapsulate and distribute poorly soluble drugs while minimising their undesired effects is significantly advantageous over traditional drug delivery. Nanocarriers can also be decorated with imaging moieties and targeting agents, further incrementing their functionality. Of recent interest as potential nanocarriers are spiropyrans; a family of photochromic molecular switches. Due to their multi-responsiveness to endo- & exogenous stimuli, and their intrinsic biocompatibility, they have been utilised in various drug delivery systems (DDSs) to date. In this review, we provide an overview of the developments in spiropyran-based DDSs. The benefits and drawbacks of utilising spiropyrans in drug delivery are assessed and an outline of spiropyran-based drug delivery systems is presented.